The relationship nutritional status with incidence of anemia in adolescent girls at At-Taqwa Islamic Boarding School - Harahap, Tapianna Sari; Rahmah, Hasni; Apriani, Suci Saftari; Hendianti, Ajeng (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Adolescent developmental growth must be met with nutritional resources. This is sometimes ignored, causing health problems such as anemia.Objective: To determine the nutritional status of the incidence of anemia in adolescent girls.Methods: The research was conducted at At-Taqwa Islamic Boarding Schoo Cilaku District Cianjur Regencyl, quantitative analytical research with a cross-sectional approach in 2023. The sample size was 52 respondents, using a random sampling technique. Data collection using a questionnaire that has been tested by experts, measuring Hb levels using the Sahli method, measuring body weight using a digital step scale, and height using a stature meter. Data analysis using bivariate looking at correlation.Results: Most of the adolescent girls had a nutritional status with normal BMI as many as 29 respondents (55.8%) and most were not anemic as many as 31 respondents (59.6%). The results of statistical tests obtained a p-value of 0.000 (<0.05), meaning that there is a correlation between nutritional status and the incidence of anemia in adolescent girls.Conclusion: Fulfillment of nutritional intake, provision of information and regular check-ups will have an impact on nutritional status and the incidence of anemia in adolescent girls